Anion‐Decoordination Cell Formation Process Stabilizes Dual Electrodes for Long‐Life Quasi‐Solid‐State Lithium Metal Battery. Issue 4 (13th December 2021) - Wang, Hao‐Ran; Yang, Ya‐Nan; Bai, Fan; Zhang, Tao
Abstract: Compared with the complete replacement of liquid electrolytes by solid electrolytes, the hybrid quasi‐solid electrolyte (HQSE) has more practical application potential due to its high thermal stability and high ionic conductivity as well as good interface wettability. In this work, a HQSE film is prepared using the Li6.40 La3 Zr1.40 Ta0.60 O12 (LLZTO) nanoparticles localized composite liquid electrolyte (CLE) composed of TEGDME (0.5 m LiTFSI) organic electrolyte and Pyr14 TFSI ionic liquid. The HQSE film exhibits high ionic conductivity of 1.77 × 10 −3 S cm –1 and a high Li‐ion transference number of 0.56 at 25 °C. More importantly, a formation process is designed by utilizing the oxidative decomposition of the free TFSI – anions caused by the substitution of ion cluster Li(TFSI) n +1 n − by Li(TEGDME) x + in HQSE, achieving the in‐situ construction of the stable and complete cathode electrolyte interface and solid electrolyte interface in the cathode and anode simultaneously, and benefiting from the liquid electrolyte being confined to the surface of LLZTO particles, the HQSE film finally exhibits high stability to the dual electrodes, ensuring that the quasi‐solid‐state Li metal battery exhibits capacity retention of 80% after 1000 cycles at 0.2 C rate, and 90% after 500 cycles at 0.5 C rate. Abstract : A dual‐electrode protection is realized through an anion‐decoordination cell formation process with a hybrid electrolyte. As a consequence, a long‐life Li metal battery is obtained with 1000 cycles at 0.2 C and 500 cycles at 0.5 C, which represents the top level of current quasi‐solid‐state Li metal systems.